Dietary Inclusion of Hydrolyzed Debaryomyces hansenii Yeasts Modulates Physiological Responses in Plasma and Immune Organs of Atlantic Salmon (Salmo salar) Parr Exposed to Acute Hypoxia Stress - Morales-Lange, Byron; Djordjevic, Brankica; Gaudhaman, Ashwath; Press, Charles McLean; Olson, Jake; Mydland, Liv Torunn; Mercado, Luis; Imarai, Mónica; Castex, Mathieu; Øverland, Margareth (Frontiers in Physiology, 2022)
Stress related to salmon aquaculture practices (handling, sub-optimal nutrition, diseases, and environmental problems) may compromise fish welfare. This study describes the effects of two hydrolyzed Debaryomyces hansenii yeast-based products (LAN4 and LAN6) on physiological and immune responses of Atlantic salmon (Salmo salar) parr exposed to a short hypoxia stress. A commercial-like diet (Control diet: CD) and two experimental diets (CD supplemented with 0.1% of either component LAN4 or LAN6) were fed to fish for 8 weeks. At the end of the feeding experiment, fish were exposed to 1-minute hypoxia and samples were collected at 0, 1, 3, 6, 12 and 24-hours post-stress. Results showed that while plasma cortisol reached a peak at 1-hour post-stress in CD and LAN6 groups, no significant increase in cortisol levels was detected in the LAN4 group. Moreover, LAN6 group enhanced IL-10 responses to hypoxia, when compared to control and LAN4 group. This suggests a regulation of immunosuppressive profiles in fish fed LAN4. Post hypoxia stress increased TNFα in all groups, indicating that fish may compensate for the short-term stress response by modulating innate immune molecules. The apparent suppression of hypoxia responses in LAN4 group coincided with detection of differences in goblet cells size and Muc-like proteins production in DI; and upregulation (1h post-stress) of pathways related to oxygen transport, hemoglobin complex and glutathione transferase activity, and a down-regulation of fatty acid metabolism (6h post-stress) in gills. To conclude, a one-minute hypoxia stress exposure affects the response to stress and immunity; and D hansenii-based yeast products are promising components in functional aquafeeds for salmon due to their ability to counteract possible consequences of hypoxic stress.